Efforts to Improve Students' Self-Efficacy Through the Discovery Learning Model - Khairani, Siti; Manihuruk, Waldio; Silalahi, Yulianda Ghrace; Rezky, Sri; Sugiharto, Sugiharto; Syarifah, Syarifah (EDUTEC : Journal of Education And Technology, 2024)
This research aims to enhance students' learning motivation through a self-efficacy approach. The study is conducted as Classroom Action Research (CAR) using the Kemmis and McTaggart model, which comprises four stages: planning, action, observation, and reflection. In this model, Kemmis and McTaggart integrate action and observation as a single unit, where observational outcomes serve as a basis for subsequent reflection. Reflections lead to modifications, actualized through further actions and observations in a continuous cycle. This research utilizes both primary and secondary data sources, with secondary data including school documents and archives. Results from the action evaluation in Cycle II indicate that 10 students (30.3%) demonstrated very high self-efficacy, while 24 students (69.7%) exhibited high self-efficacy, and no students were in the very low category. The average self-efficacy score rose from 92.29 in Cycle I to 94.91 in Cycle II, indicating a 2.62-point increase. These findings demonstrate a significant improvement in students' self-efficacy scores, reflecting enhanced learning motivation through this approach.